(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
Complications of arterial hypertension (AH), beginning to show a direct relationship with the level of blood pressure 145/95 mm Hg. Art., for many decades are the leading cause of death among all causes of death. Arterial hypertension, without a doubt, is the leading medical and social problem of our time, the role of which in mortality and disability of people continues to grow, despite the great attention paid to this problem by the scientific community, practitioners and authorities.